The Petta Kalie’s Contribution in The Development of Islamic Law during The Kingdom of Bone - Ridhwan, Ridhwan; A Nuzul, A Nuzul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
This article examines Petta Kalie's contribution to the development of Islamic law in the Kingdom of Bone. Petta Kalieor qadhi has the same position as an advisor or counselor to the sultan. This was similar to the qadhi al-qudhat in Baghdad, syekh Islam in Turkey, sadar-i azam in India, qadhil malikul adil in Aceh or Wali Songo in Java. This study uses a historical approach to understanding the Islamic law as an analytical tool by looking at Petta Kalie as a collective history that contributes to the development of the Islamic law. The study concluded that there were four contributions of Petta Kalie in the development of Islamic law: affirming the integration of sara’ (Islamic law) and ade’ (adat), such as the sompa, mappacci, barzanji and meppanre tamme traditions. The internalization of the Islamic law with the style of Syafi’i school of thought  was carried out by Patte Kalie assisted by puang imang, katte’, bilal, doja and amil who are in charge of teaching and disseminating the Islamic laws such as marriage, divorce, reconciliation, inheritance distribution, and the management of zakat. In addition, Petta Kalie also promotes women’s equality in the Islamic law, supports female Sultanah to appear as kings and initiates education in studying Islamic sciences especially for women called makkamisi’. Finally, a legal fatwa related to resistance to the Netherlands and refusal to cooperate with them. Some of these arguments and findings are indisputable historical facts that Petta Kalie made a major contribution to the development of Islamic law in the Bugis Bone society.